Living with a Sibling who is on the Autism Spectrum: The Siblings’ Perspective - Calleja, Colin; Agius, Maia-Rhys (British Journal of Healthcare and Medical Research, 2025)
This study explores the lived experiences of neurotypical siblings who have a brother or sister on the autism spectrum. Drawing on qualitative case studies of three adolescent siblings, the research investigates the emotional, social, and developmental impacts of these relationships. Through semi-structured interviews, the study identifies themes such as caregiving responsibilities, the emotional burden of unequal attention, and future caregiving concerns. The findings highlight both the challenges and growth opportunities associated with these sibling relationships. By examining these experiences within the unique cultural context of Malta, this study contributes to the broader discourse on inclusion and family dynamics in autism spectrum disorder (ASD). Implications for educational systems, family support programmes, and future policy developments are discussed.